2019
DOI: 10.1136/jmedgenet-2018-105793
|View full text |Cite
|
Sign up to set email alerts
|

H2AFY promoter deletion causes PITX1 endoactivation and Liebenberg syndrome

Abstract: BackgroundStructural variants (SVs) affecting non-coding cis-regulatory elements are a common cause of congenital limb malformation. Yet, the functional interpretation of these non-coding variants remains challenging. The human Liebenberg syndrome is characterised by a partial transformation of the arms into legs and has been shown to be caused by SVs at the PITX1 locus leading to its misregulation in the forelimb by its native enhancer element Pen. This study aims to elucidate the genetic cause of an unsolved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…Recently, Cassini et al reported a deep intronic variant in IGHMBP2 shown to lead to nonsense mediated decay via activation of a cryptic splicing site in a patient with Charcot-Marie-Tooth [34]. As part of a more complex mechanism, Kragesteen et al described a deletion in the first noncoding exon of H2AFY that leads to abnormal expression of Pitx1 and Liebenberg syndrome [35].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Cassini et al reported a deep intronic variant in IGHMBP2 shown to lead to nonsense mediated decay via activation of a cryptic splicing site in a patient with Charcot-Marie-Tooth [34]. As part of a more complex mechanism, Kragesteen et al described a deletion in the first noncoding exon of H2AFY that leads to abnormal expression of Pitx1 and Liebenberg syndrome [35].…”
Section: Discussionmentioning
confidence: 99%
“…3 H and I ), suggesting that Myb is essential for EryD-specific distal enhancer activation. Disruption, inversion, or insertion of enhancers can perturb tissue-specific chromatin architecture and lead to inappropriate expression of target gene ( 43 47 ). Here, CRISPR/Cas9-mediated deletion of selected enhancers resulted in a striking decrease in target gene expression in adult stage MEL cells, but not in mESC-derived erythroblasts ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This is because in forelimbs the Pen enhancer is sequestered by other contacts or titrated out by the closely located H2afy (Macroh2a1) gene promoter, which prevents interactions with Pitx1. In the hindlimbs, the enhancer escapes its local 3D domain to interact with the Pitx1 promoter, thus allowing transcription and the conferral of hindlimb identity (Kragesteen et al, 2018(Kragesteen et al, , 2019.…”
Section: A Single Enhancer Dominates Regulationmentioning
confidence: 99%